Applying the contact element for simulation of interaction between drillstring and holewall - Hao, Le Phuoc; Dung, Ta Quoc (Vietnam Journal of Mechanics, 2003)
The purpose of research is to create a contact element in order to simulate the dynamics contact phenomenon of drillstring and drillhole. The contact element is located at some selected node along the drillstring. In the contact element, not only transverse friction force but also the longitudinal friction forces are taken into account. The element stiffness and damping matrices are derived explicitly. This element is implemented in general and powerful multi-body dynamics analysis software, namely Mecano module of Samcef. Therefore, many computational aspects of the Mecano software, for example the nonlinear beam element, the implicit time integration method, can be directly applied.